SM22α inhibits vascular inflammation via stabilization of IκBα in vascular smooth muscle cells. (July 2015) - Shu, Ya-Nan; Zhang, Fan; Bi, Wei; Dong, Li-Hua; Zhang, Dan-Dan; Chen, Rong; Lv, Pin; Xie, Xiao-Li; Lin, Yan-Ling; Xue, Zhen-Ying; Li, Haibo; Miao, Sui-Bing; et al.
Abstract: Smooth muscle (SM) 22α, an actin-binding protein, is down-regulated in atherosclerotic arteries. Disruption of SM22α promotes arterial inflammation through activation of reactive oxygen species (ROS)-mediated nuclear factor (NF)-κB pathways. This study aimed to investigate the mechanisms by which SM22α regulates vascular inflammatory response. The ligation injury model of SM22α −/− mice displayed up-regulation of inflammatory molecules MCP-1, VCAM-1, and ICAM-1 in the carotid arteries. Similar results were discovered in human atherosclerotic samples. In vitro studies, overexpression of SM22α attenuated TNF-α-induced IκBα phosphorylation and degradation, accompanied by decreased NF-κB activity and reduced inflammatory molecule expression. Using coimmunoprecipitation, we found that SM22α interacted with and stabilized IκBα in quiescent VSMCs. Upon TNF-α stimulation, SM22α was phosphorylated by casein kinase (CK) II at Thr139, leading to dissociation of SM22α from IκBα, followed by IκBα degradation and NF-κB activation. Our findings demonstrate that SM22α is a phosphorylation-regulated suppressor of IKK–IκBα–NF-κB signaling cascades. SM22α may be a novel therapeutic target for human vascular diseases and other inflammatory conditions. Highlights: SM22α inhibits the inflammation response in VSMCs. SM22α interacts with IκBα to inhibit NF-κB nuclear translocation in VSMCs. CKII-mediated SM22α phosphorylation switches IκBα–NF-κB signaling in VSMCs.